Perancangan Video Company Profile Sebagai Media Promosi Pendidikan Gratis Pada SMP–SMA Khadijah Islamic School di Jakarta Selatan - Sholehah, Umi Idza Adhati (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to design a video company profile for Khadijah Islamic School as a visual communication medium that not only conveys institutional information but also builds emotional closeness with the community through a humanistic approach. This approach emphasizes the values of empathy, social concern, and a vision of the future for students so that the message is easier to understand and remember. The method used is the design of visual communication media, which includes needs analysis to identify promotional issues, data collection through field observations and interviews with the school, creative concept formulation, storyboard preparation, video production process, and media evaluation. The visual concept is designed by combining inspirational narratives, documentation of student activities, and testimonials to reinforce the credibility and appeal of the message. The results of the design show that the company profile video is capable of functioning as an informative, persuasive, and emotional promotional medium. This medium has the potential to increase public awareness of the existence of Khadijah Islamic School, encourage donor participation, and expand the reach of beneficiaries of free education programs. Thus, the company profile video can be an effective communication strategy to support the sustainability of social-based educational institutions.